Environmental Adaptability Design of Drive Motor System for Electric Vehicle - TIAN Kuishen; LIU Chunxiu; WANG Zhengyu; HU Yongfeng; XIN Benyu (Kongzhi Yu Xinxi Jishu)
As a key component of electric vehicles, the environmental adaptability of drive motor system determines the reliability level of the electric vehicle. Based on the analysis of environmental stress subjected to drive motor system, it presented the influence of environmental stress on the drive motor system, discussed the reference values of several environmental parameters and proposed methods of environmental adaptability design.